Granulocyte Colony-Stimulating Factor Prevents Ischemia/Reperfusion-Induced Ovarian Injury in Rats: Evaluation of Histological and Biochemical Parameters. (October 2019) - Hortu, Ismet; Ozceltik, Gokay; Sahin, Cagdas; Akman, Levent; Yildirim, Nuri; Erbas, Oytun
Granulocyte colony-stimulating factor (G-CSF) is a glycoprotein commonly used in the field of medicine to treat neutropenia. Granulocyte colony-stimulating factor has also crucial roles in ameliorating the ischemia/reperfusion (I/R) injury in particular tissues. In this study, we aimed to investigate the protective effect of G-CSF on ovarian damage in experimental ovarian I/R injury. Thirty adult female rats were used. Rats were separated randomly into 5 groups; Group 1: sham group (abdominal wall was opened and closed surgically), Group 2: torsion group with 3-hour ischemia using vascular clips. Group 3: torsion + G-CSF group with 3-hour ischemia 30 minutes after the administration intraperitoneal (i.p.) of 100 µg/kg of G-CSF. Group 4: torsion-detorsion group with 3 hour ischemia and 3 hour reperfusion. Group 5: torsion-detorsion + G-CSF group with 3 hour ischemia followed by 100 µg/kg of G-CSF i.p. administration 30 minutes prior to 3 hour of detorsion/reperfusion. Ovarian tissue damage was scored on histopathology. Ovarian tissue malondialdehyde (MDA) was measured biochemically. In comparison with the sham group, both the torsion and torsion-detorsion groups had significantly higher scores for follicular degeneration, vascular congestion, edema, hemorrhage, and leukocyte infiltration ( P < .05). When compared group torsion-detorsion + G-CSF to group torsion-detorsion, parameters aforementioned significantly decreased in group torsion-detorsion + G-CSF ( P < .05). Granulocyte colony-stimulating factor has also decreased MDA levels notably both in the torsion + G-CSF and torsion-detorsion + G-CSF groups ( P < .05, P < .01). Our experimental study suggests that G-CSF can be a novel agent for the treatment of ovarian I/R injury.